Hemispheric dominance in HVC is experience-dependent in juvenile male zebra finches - Sophia Y. Frank; Jesse L. Hunt; Andrea J. Bae; Napim Chirathivat; Sima Lotfi; Sahitya C. Raja; Sharon M. H. Gobes (Scientific Reports, 2024)
Abstract Juvenile male zebra finches (Taeniopygia guttata) must be exposed to an adult tutor during a sensitive period to develop normal adult song. The pre-motor nucleus HVC (acronym used as a proper name), plays a critical role in song learning and production (cf. Broca’s area in humans). In the human brain, left-side hemispheric dominance in some language regions is positively correlated with proficiency in linguistic skills. However, it is unclear whether this pattern depends upon language learning, develops with normal maturation of the brain, or is the result of pre-existing functional asymmetries. In juvenile zebra finches, even though both left and right HVC contribute to song production, baseline molecular activity in HVC is left-dominant. To test if HVC exhibits hemispheric dominance prior to song learning, we raised juvenile males in isolation from adult song and measured neuronal activity in the left and right HVC upon first exposure to an auditory stimulus. Activity in the HVC was measured using the immediate early gene (IEG) zenk (acronym for zif-268, egr-1, NGFI-a, and krox-24) as a marker for neuronal activity. We found that neuronal activity in the HVC of juvenile male zebra finches is not lateralized when raised in the absence of adult song, while normally-reared juvenile birds are left-dominant. These findings show that there is no pre-existing asymmetry in the HVC prior to song exposure, suggesting that lateralization of the song system depends on learning through early exposure to adult song and subsequent song-imitation practice.